Gut Microbiota May Not Be Fully Restored in Recovered COVID-19 Patients After 3-Month Recovery - Tian, Yu; Sun, Kai-yi; Meng, Tian-qing; Ye, Zhen; Guo, Shi-meng; Li, Zhi-ming; Xiong, Cheng-liang; Yin, Ying; Li, Hong-gang; Zhou, Li-quan (Frontiers in Nutrition, 2021)
Coronavirus disease 2019 (COVID-19) has infected over 60 million people worldwide. Besides developing the therapeutics and vaccines, the evaluation of sequelae in recovered patients is also important. Recent studies have indicated that COVID-19 has the ability to infect intestinal tissues and to trigger the alterations of gut microbiota. However, whether these changes in gut microbiota persist into the recovery stage remains largely unknown. Here, we recruited seven healthy Chinese men and seven recovered COVID-19 male patients with an average of three months after discharge, and analyzed their fecal samples by 16S rRNA sequencing analysis to identify the differences in gut microbiota. Our results suggested that the gut microbiota of male recovered patients differed remarkably compared with healthy controls, in which a significant difference in Chao index, Simpson index, and β diversity were observed. And the relative abundance of several bacterial species differed clearly between two groups, characterized by enrichment of opportunistic pathogens and depletion of anti-inflammatory bacteria in producing short chain fatty acids. Similar conclusion may be applicable to female recovered patients. These findings provide preliminary clues supporting that the imbalanced gut microbiota may persist in recovered patients, highlighting the importance of continuous monitoring gut health in people recovered from COVID-19.